2020
DOI: 10.20448/journal.500.2020.72.114.123
|View full text |Cite
|
Sign up to set email alerts
|

HRM and its Impact on Employee Happiness: An Empirical Study on Sri Lankan Employees

Abstract: A systematic empirical study was carried out with regard to Human Resource Management (HRM) and Employee Happiness owing to little research done, contextual gap and intellectual curiosity of authors. Objectives of the study were (1) to find the degree of happiness of Sri Lankan employees under study; (2) to find the degree of HRM practices in the organizations where employees are working under study; and (3) to investigate whether there is any positive and significant impact from HRM on employee happiness. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Perera and Madagamage (2018) say that it is the obligation of the management, particularly top managers to consider improving the job satisfaction of employees. According to Opatha and Uresha (2020) found that there is a significant positive impact from HRM on employee happiness and this can be further described in statistically as 45.6% of the variance in employee happiness is explained by human resource management.…”
Section: Discussionmentioning
confidence: 98%
“…Perera and Madagamage (2018) say that it is the obligation of the management, particularly top managers to consider improving the job satisfaction of employees. According to Opatha and Uresha (2020) found that there is a significant positive impact from HRM on employee happiness and this can be further described in statistically as 45.6% of the variance in employee happiness is explained by human resource management.…”
Section: Discussionmentioning
confidence: 98%
“…Work from home is measured by four dimensions (productivity, attitude, social, and situational factors in the form of resources and distractions) adopted from measurements developed by Neufeld & Fang and adapted by Irawanto et al [1] Happiness is a positive emotion that a person has. In contrast, happiness at work is defined as a feeling of joy and meaning associated with various aspects of employee life, such as personal life, career, and social life [17] . Happiness at work can be explained through a combination of job, workplace, and worker characteristics [18] .…”
Section: Literature Review the Relationship Between Work From Home An...mentioning
confidence: 99%
“…Work-life balance refers to the emotional state in which individuals experience satisfaction by harmoniously managing their work responsibilities and personal lives, including family commitments. This achievement can lead to feelings of happiness and fulfillment associated with different aspects of an employee's life, such as personal relationships, career, and social interactions [17] , [23] . Achieving an ideal balance between a worker's primary focus and lifestyle is known as work-life balance [24] .…”
Section: The Relationship Between Work From Home and Work Life Balancementioning
confidence: 99%
See 1 more Smart Citation
“…In remote work, workforce is allowed to work from convenient places other than the office by utilizing advanced technology like internet, video conferencing, e-mail etc. (Uresha, 2020). In employees' point of view, remote work is a job perk and more than half of them considered it as an arrangement to improve work-life balance.…”
Section: Introductionmentioning
confidence: 99%